Restructuring the Resilience of Supervisees During the Early Stages of Supervision: A Case Study Incorporating Play Therapy for Future Implementation - Alice Erni Husein; Mariska Putri Pratiwi; Zakarias Situmorang (CV. RADJA PUBLIKA, 2026)
This study explores the role of clinical supervision in restructuring supervises’ resilience during the early stages of play therapy training. Despite extensive research on client outcomes, limited attention has been given to supervises’ psychological and professional development. This study addresses this gap by examining how supervision contributes to supervisees’ behavioural and emotional transformation. A qualitative case study approach was employed, analysing 22 supervision sessions through processed diary transcriptions. Methodological triangulation was applied by integrating qualitative analysis with an artificial intelligence–based instrument, FotoKarakter, to enhance validity and provide additional behavioural insights. The findings reveal a significant transformation in supervises’ personality, shifting from task-oriented to people-oriented characteristics, as illustrated through a U-shaped developmental trajectory. The supervision triangle framework plays a crucial role in facilitating reflective learning, emotional regulation, and professional identity formation. This study contributes to the advancement of play therapy by repositioning supervision as a critical mechanism not only for client outcomes but also for supervisee development. Practically, the findings highlight the importance of structured supervision and the integration of objective measurement tools in strengthening supervises’ resilience and professional competence.